Hearing Impairment and the Amelioration of Avoidable Medical Error: A Cross-Sectional Survey. Issue 3 (April 2021) - Henn, Patrick; O'Tuathaigh, Colm; Keegan, Darrelle; Smith, Simon
Abstract : Objectives: Hearing loss contributes to suboptimal medical treatment. We investigated the nature and magnitude of potential health-care harm of hearing loss alone on a patient's understanding of medical consultations, investigations, and treatments of health conditions unrelated to their hearing loss. Methods: A cross-sectional, questionnaire-based design of a convenience sample of students with hearing loss, registered with the institutional disability support service in 8 Irish and 15 UK third-level institutions. Content analysis of open-ended item responses identified and coded emergent themes. Closed-ended questionnaire items recorded demographic and clinically relevant characteristics. Results: Ninety-five responses were received and analyzed. Fifty-six (58.9%) indicated "yes" to mishearing a physician/nurse in a hospital. Approximately 60.7% identified this in relation to consultation content; 33.9% mishearing; and 21.4% misinterpreting what was said, including diagnosis, guidelines and advice, and matters relating to medications. Approximately 22.3% indicated physician/nurse-patient communication failures; 19.6% identified failure to initiate/maintain eye contact, turning away from the patient, speaking while wearing surgical masks, excluding the possibility of lip reading. Approximately 7.1% identified speaking in too low a volume or too fast. Concerning common words misheard or misinterpreted, 23.2% identified phonological similarity such as similar sounding words and numbers, 7.4% discrimination of unvoiced consonants. Similar findings emerged in GP clinics. Conclusions: Most hearing-impaired students experienced difficulty in understanding health-care professionals in a hospital and general practice setting. This underscores the importance for health-care providers to identify hearing-impaired patients and to augment communication using visual aids, a quite environment and optimizing lip reading communication.